PENGARUH SMALL GROUP DISCUSSION TERHADAP PENERIMAAN DIRI PASIEN GAGAL GINJAL KRONIS YANG MENJALANI HEMODIALISIS : - - Novian Yustiasari (LPPMK STIKES Widyagama Husada, 2022)
The negative impact of decreased body functions and psychosocial changes in patients with CKD is self-acceptance that low. Small group discussion (SGD) is a method to increase self-acceptance. This study aims to determine the effect of SGD on self-acceptance of CKD patients undertaking hemodialysis at RSUD Dr. Saiful Anwar Malang. The design of this study are pre experimental and design used is th e one group pre-test post-test . Instrument is used is my sheet questionnaire. The sample in this study was 20 patients with CKD who underwent therapy hemodialysis by using technique purposive sampling . The results of the study obtained that 50% of self- acceptance before the SGD was carried out had low self-acceptance, and none had very high self-acceptance criteria. Meanwhile, after the SGD was done , the patient's self-acceptance became the majority of respondents, 55% high self-acceptance. Based uji Wilcoxon results significantly (P <0.05 ). The study says that terdapat influence SGD self-acceptance in patients with CKD who undertaking hemodialysis which caused their support between the patient and the similarity of the feelings of patients to exchange experiences, share about how to resolve the problem . Suggestions subsequent studies add to the frequency of meetings to conduct small group.